Aberrant Morphologic Patterning of Combined Sagittal and Metopic Craniosynostosis. Issue 6 (September 2021) - Dinis, Jacob; Junn, Alexandra; Lu, Xiaona; Lopez, Joseph; Persing, John
Abstract : Abstract: Combined sagittal and metopic craniosynostosis is an uncommon condition that may result in a wide spectrum of cranial morphologies. This occurs as a result of the compound effects of both prematurely fused sutures. The authors present an incidence of sagittal craniosynostosis with a specific altered head morphology, and delayed diagnosis that the authors believe occurred due to structural changes associated with concurrent metopic suture synostosis This patient underscores the limitations of relying on classic diagnostic patterns and highlights the critical role of noninvasive imaging in the diagnosis of craniosynostosis.